Sistem Kontrol Suhu Pada Destilator Untuk Mengukur Kadar Air Limbah Pabrik Udang Berbasis Arduino - Abhiyaksa, Mahindra; Adi Mulyadi; Widhi Winata Sakti (Journal Electric Field, 2025)
This paper discusses the design and temperature control system for shrimp factory wastewater distillation. During the distillation process, wastewater is heated to condense and separate the resulting water vapor. Therefore, a temperature control system is proposed to ensure efficiency. The effectiveness of temperature control in the distillation process is assessed based on changes in temperature. Changes in initial and final temperatures were observed in the distillation process using 50ml-250ml samples and a temperature variation of 34°C–101°C. Test results showed that a 50ml sample reached a maximum temperature of 82°C, producing 9ml of condensate. A 100ml sample, with a maximum temperature of 84°C, produced 19ml of condensate. A 150ml with a maximum temperature of 92°C. Producing 60 ml of condensate, the 200 ml sample reached a maximum temperature of 85°C, producing 60 ml of condensate, and the 250 ml sample reached a maximum temperature of 101°C, producing 60 ml of condensate. The initial TDS value for the 50–250 ml samples remained constant at 1,683 ppm. After distillation, the TDS values for each sample were 319 ppm for the 50 ml sample, 671 ppm for the 100 ml sample, 93 ppm for the 150 ml sample, 86 ppm for the 200 ml sample, and 129 ppm for the 250 ml sample. The contribution of the research is that the control system can reduce the impact of waste on industry by regulating the temperature on the Peltier.